Short‐term outcomes after surgical resection for colorectal cancer in South Australia. Issue 2 (2nd August 2016) - Beckmann, Kerri; Moore, James; Wattchow, David; Young, Graeme; Roder, David
Abstract: Rationale, aims and objective: Short‐term outcomes (unplanned readmission, post‐surgical complication rates, 30‐day and 90‐day post‐surgical mortality) are often used as indicators of quality of surgical care for colorectal cancer (CRC). Differences in these immediate outcomes can highlight disparities in care across patient subpopulations. This study aimed to document short‐term outcomes following major surgery for CRC and to identify whether there were any sociodemographic differences across South Australia (SA). Methods: This population‐based study included all CRC resections among SA residents diagnosed with CRC aged 50–79 years in 2003‐2008 ( n  = 3940). Clinical, treatment, comorbidity and outcomes data were compiled through linkage of administrative and surveillance datasets across SA. A retrospective cohort design was used to examine short‐term outcomes including post‐operative complications, 28‐day emergency readmission and 30‐day and 90‐day mortality. We used multivariable logistic regression to identify factors associated with each outcome. Results: Post‐operative complications occurred in 28% of cases. Thirty‐day and ninety‐day mortality were 1.3% and 3%, respectively. Later stage, older age, multiple comorbidities and emergency admissions were associated with poorer short‐term outcomes. Risk of complications was lower among patients from higher socio‐economic areas (OR = 0.77, 95%CI 0.62‐0.98). Risk of 30‐day mortality was higher among non‐metropolitan patients (OR = 2.33, 95%CI 1.22‐4.46). Post‐operative complications increased the risk of emergency readmission and short‐term mortality. Conclusions: Short‐term outcomes following CRC surgery may be improved through strategies to increase earlier detection and reduce emergency admissions. Socioeconomic and regional disparities require further examination of health system factors.